Comparison of ultrathin CoTiO3 and NiTiO3 high-k gate dielectrics - Pan, TM; Lei, TF; Chao, TS (My University, 2001)
High-k cobalt-titanium oxide (CoTiO3) and nickel-titanium oxide (NiTiO3) were formed by directly oxidizing sputtered Co/Ti and Ni/Ti film. Al/CoTiO3/Si3N4/Si and Al/NiTiO3/Si3N4/Si capacitor structures were fabricated and measured. The effective dielectric constant (k value congruent to 45) with buffer layer for CoTiO3 is larger than that of NiTiO3. In addition, CoTiO3 depicts excellent electrical properties at the same time. This metal oxide thus appears to be a very promising high-k gate dielectric for future ultralarge scale integrated devices. (C) 2001 American Institute of Physics.